Genetic relationships among species and cultivars of Pistacia using RAPDs and AFLPs - Katsiotis, Andreas; Hagidimitriou, Marianna; Drossou, Anna; Pontikis, Constantinos; Loukas, Michael (My University, 2003)
The genus Pistacia (Anacardiaceae) includes 11 species divided into four sections, according to leaf characters and nut morphology. Recently two monophyletic groups have been proposed by using cpDNA, Lentiscus and Terebinthus, containing evergreen and deciduous species, respectively. In the present work molecular markers, derived from two different methods, RAPD and AFLP, are used to study the relationships of native and introduced Pistacia species present in Greece. According to the cophenetic correlation coefficients best results for both methods were obtained by using the Jaccard algorithm and the UPGMA clustering method. However, phenograms were constructed using the NJ method (rcs=0.987 for RAPDs and rcs=0.982 for AFLP), since it is less sensitive against varying mutation rates. Correlation among the genetic similarity (GS) matrices for the two methods was high (r = 0.941). The AFLP and RAPD phenograms were comparable with minor clustering differences. According to our results, two main branches are obtained, one containing the evergreen species P. lentiscus and the resin producing P. lentiscus cv. Chia (cultivated only in the island of Chios), and the other branch containing the deciduous species P. terebinthus, P. palaestina and P. vera. P. chinensis was clustered either with the evergreen species (RAPD data) or with the deciduous species (AFLP data). P. palaestina is clustered to P. terebinthus and can be considered as a subspecies of P. terebinthus, since its GS values are close or smaller than GS values of entries within species (P. vera). The four female cultivars were found to have a narrow genetic basis, probably related to cultivar 'Nazareth' with Syrian origin.
Keywords: AFLP; Molecular markers; NJ; Principle Coordinate Analysis; RAPD; UPGMA